ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLES SYNTHESIZED BY HYDROTHERMAL TECHNIQUE - Abduljabbar, Shireen Taily; Abbas, Tariq Abdul-Hameed (Science Journal of University of Zakho, 2025)
In this work, Ag NPs were synthesized via a hydrothermal method using silver nitrate (AgNO3) as precursor material. The impact of PVP concentration on the particle size distribution and surface morphology of Ag NPs in the hydrothermal reaction was studied. The obtained Ag NPs were characterized by UV–Vis, XRD, FESEM, and FTIR measurements. The calculated values of Eg from the absorption peaks of the UV/Vis- spectra were found to be increased from 1.70 eV to 1.87 eV with increasing the concentration of PVP from 0.2 mol/L to 0.5 mol/L. XRD measurements revealed that the Ag NPs are highly crystalline. The FESEM observation results indicated that the optimized synthesized Ag NPs are spherical with an average size of 140 nm. The FTIR results confirmed the Ag NPs formation with presence of several functional groups in Ag NP and pure PVP. The study evaluated the antibacterial activity of Ag NPs based on the diameter of the inhibition zone in the agar well diffusion method. The results indicated that the characteristics and antibacterial activity of Ag NPs could be optimized by altering the concentration of PVP used as a stabilizer. The Ag NPs synthesized without the addition of PVP showed antibacterial activity on both gram-negative bacterium Escherichia coli (11 to 12) mm and gram-positive bacterium Staphylococcus aureus (12 to 13) mm, meanwhile with using PVP, there is no inhibitory activity towards gram-negative bacteria but showed antibacterial activity on gram-positive (25) mm. The stability of Ag NPs has been investigated by measuring the absorption spectrum of the PVP-Ag NPs, which was found to be stable for nearly 3 months. Synthesis of stable Ag NPs is necessary for later use in the required application.
Keywords: Silver Nanoparticles; Hydrothermal Technique; Polyvinylpyrrolidone Stabilizer; Size Control; Antibacterial Activity